Transcriptome Profiling of Porcine Naïve, Intermediate and Terminally Differentiated CD8+ T Cells - Lagumdzic, Emil; Pernold, Clara; Viano, Marta; Olgiati, Simone; Schmitt, Michael W.; Mair, Kerstin H.; Saalmüller, Armin (Frontiers in Immunology, 2022)
The pig has the potential to become a leading research model for human diseases, pharmacological and transplantation studies. Since there are many similarities between human and pig organism, especially concerning anatomy, physiology and metabolism, there is necessity for a better understanding of the porcine immune system. In adaptive immunity, cytotoxic T lymphocytes (CTLs) are essential for host defense. However, most data on CTLs come from studies in mice, non-humane primates and humans, while detailed information about porcine CD8+ CTLs is still sparse. Aim of this study was to analyze three subsets of porcine CD8β+ CTLs by using high-throughput next-generation sequencing technology. Specifically, we described transcriptional profiles of subsets defined by their CD11a/CD27 expression pattern, postulated as naïve or progenitors (CD8β+CD27+CD11alow), intermediate differentiated (CD8β+CD27dimCD11a+), and terminally differentiated cells (CD8β+CD27-CD11a++). Cells were analyzed in ex vivo condition as well as upon in vitro stimulation with ConA and PMA/Ionomycin. Our analyses show that the highest number of differentially expressed genes was identified between naïve and terminally differentiated CTLs, underlining their difference in gene expression signature and respective differentiation stages. Moreover, genes related to early (IL7-R, CCR7, SELL, TCF7, LEF1, BACH2, SATB1, ZEB1 and BCL2) and late (KLRG1, TBX21, PRDM1, CX3CR1, ZEB2, ZNF683, BATF, EZH2 and ID2) stages of CD8+ T-cell differentiation were highly expressed in the naïve and terminally differentiated CTLs, respectively. Intermediate differentiated CTLs shared a more comparable gene expression profile associated with later stages of T-cell differentiation. Genes associated with cytolytic activity (GNLY, PRF1, GZMB, FASL, IFNG and TNF) were highly expressed in terminally and intermediate differentiated CTL subsets, while naïve CTLs lacked expression even after in vitro stimulation. Overall, PMA/Ionomycin stimulation induced much stronger upregulation of genes compared to stimulation with ConA. Taken together, we provided comprehensive results showing transcriptional profiles of three differentiation stages of CTLs. In addition, our study provides a powerful toolbox for a new way to characterize immune cells of the porcine immune system.